Lead, copper and zinc content in soft tissues and shells of blood Cockle (anadara granosa) from coastal water of tanjung balai Asahan regency north sumatera province - Hardy PH Simanjunntak; Yusni Ikhwan; Bintal Amin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted in Januari 2014. Samples of blood cockle were taken from onthe waters of Tanjung Balai Asahan North Sumatera. The purpose of this study was to analyzethe metal content of Pb, Cu and Zn in soft tissues and shells of blood cockle with different bodysize, determine the different concentration of Pb, Cu and Zn in soft tissues and shell, determinerelationships of metal content in soft tissues and shells with the body size and to determine thesafety comsumption of blood cockle. Pb and Cu content in the shells were higher than softtisssues whilst Zn was higher in the soft tissues. The average metal content in soft tissues weredifferent by the size where Pb conteten was higher in the small size (1,79 μg/g ), Cu in smallsize (9,69 μg/g) and Zn also in small size (1.227, 81 μg/g). Mean while the average , Pb contentin shells was higher in the large size (8,26 μg/g) , Cu in medium size ( 19,24 μg/g), and Zn wasin the medium size too (1.017, 02 μg/g).Keyword: Heavy metal, A,granosa, Shell, Soft tissue, Tanjung Balai Asahan